Microstructural and elasto-plastic material parameters identification by inverse finite elements method of Ti(1−x)AlxN (0<x<1) sputtered thin films from Berkovich nano-indentation experiments - Pac, M.-J.; Giljean, S.; Rousselot, C.; Richard, F.; Delobelle, P. (Thin solid films, 2014)
The mechanical properties of Ti(1−x)AlxN (0<x<1) films of different thicknesses deposited by r.f. reactive magnetron sputtering on Si and high speed steel substrates have been investigated. The as-deposited coatings have been characterized by X-ray diffraction, atomic force microscopy, four-probe electric resistivity method, mechanical deflection of cantilever beams and Berkovich nano-indentation tests associated with inverse finite elements analysis. The coatings with x<0.58–0.59 present a cubic structure whereas for x>0.7 a hexagonal structure is observed. Between these two compositions cubic and hexagonal structures coexist. The roughness depends on the film thickness and on the Al content and a minimum associated to a very fine microstructure is clearly observed in the two-phase coatings. The electric resistivity sharply increases as soon as the hcp structure appears (x~0.6). The mean residual stresses are compressive, except for the AlN coating, and present a minimum at the neighborhood of x~0.64 where a mixed structure is observed. The indentation modulus M and the Berkovich hardness HB greatly depend on the Al content and a progressive decreasing has been observed for 0.58<x<0.7. For the M evolution, a simple model taking into account the stiffness coefficients of TiN and AlN structures, the mean residual stress level and the variations of the lattice parameters in the two structure domains is proposed. Knowing the elastic properties of these films, inverse finite elements analysis of the indentation curves considering a simple isotropic linear elasto-plastic behavior allows, as a function of the composition, the yield stress σY and the linear hardening coefficient Hp⁎ to be estimated. σY and Hp⁎ are in the ranges 4.2 to 6.8GPa and 60 to 400GPa, respectively. The maximum value of Hp⁎/σY which characterizes the ability of these coatings to exhibit plastic strain hardening is maximum for x=0.5 and 0.6. The quality of the estimation was discussed through a practical identifiability study and quantified using an identifiability index. Tip radius and elasticity of the Berkovich indenter are two very relevant parameters to improve identifiability and correctly extract the plastic parameters of the behavior law. Scratch crack propagation resistance shows an evolution similar to those of Hp⁎/σY. •A transition from cubic to hexagonal structures occurs for 0.58–0.59<x(%Al)<0.7.•Indentation modulus, hardness and residual stress greatly depend on the structure.•Yield stress and hardening rate are determined by inverse finite elements method.•The quality of the estimations is discussed through a practical identifiability index.•The set of these quantities exhibit a sharp transition between x=0.6 and 0.7.